Quality of life in children with kidney transplant: Systematic review - Noélia Souza Santos Araújo; Rogério Rodrigues Floriano Pereira; Dayana Fram; Paula Hino; Maria Cristina Barbosa Longo; Monica Taminato
ABSTRACT Objective: To identify in the literature studies that evaluate the quality of life in pediatric patients with kidney transplant through use of specific, validated instruments in Pediatrics. Method: Systematic review of the literature with searches conducted in the following databases: Medline, PubMed, LILACS, CINAHL, SciELO and Cochrane Library. Main keywords: Quality of life, Kidney transplantation and Pediatrics. Results: A total of 366 studies were selected and eight observational studies were included that evaluated the quality of life of children with kidney transplant by means of evaluation instruments of quality of life. Conclusion: The quality of life of children with kidney transplant is inferior compared to healthy children. The post-transplant period presents better results compared to pre-transplant children. The identification of mental, physical and social conditions related to the quality of life of this population allows for better planning the assistance provided to them.